Ernest Rutherford and the Birth of Modern Physics: Matthew Wright. 2025. Oratia Books. ISBN 978-1-99-004268-3 - Dickson, Benjamin (New Zealand Science Review, 2025)
Book Review: Ernest Rutherford and the Birth of Modern Physics.